The Determinants of Movie-Induced Tourism in Creating Visit Intention Based on Audience Personal Motivation (A Study on Indonesia’s Box Office Movie) - Parahiyanti, Cesya Rizkika; Purwanto, BM (JDM (Jurnal Dinamika Manajemen), 2021)
This research aims at identifying movie-induced tourism in terms of business related to audience personal motivation using a study on movie Ada Apa Dengan Cinta (AADC) 2. It uses qualitative research with a descriptive approach. The results of the in-depth interviews from 17 respondents are analyzed using conventional content analysis that would later raise the emergent themes to support the identification of movie-induced tourism in the study of AADC 2. The results of this study indicate that AADC 2 has a function to influence audiences traveling decisions on the featured locations after watching the movie, even though the film itself is not intended to promote a particular destination. Audience personal motivations in this study are grouped into two, namely general personal motivation and specific personal motivation. There are also considered factors of audiences that influence their decision to travel to the featured locations in the movie. The audience also expresses some assessments and behavioral intentions after they visited the sites. With these results, this study is expected to provide an overview of the relevant business players, such as tourism office, Destination Marketing Organizations (DMO), and movie production companies, about tourist behaviors in Indonesia.